DETERMINING THE PERCEPTIONS OF THE PRE-SERVİCE SCIENCE TEACHERS ON THE ENVIRONMENT AND ENVIRONMENTAL PROBLEMS THROUGH THE WORD ASSOCIATION TEST - UZUN, Belgin; İRİS, Hanife (SSD Journal, 2023)
In this study, it is aimed to examine pre-service science teachers’ perceptions of environment and environmental problems by using the word association test. The research was carried out with 32 teacher candidates studying at Sakarya University Faculty of Education, Department of Science Education in the 2021-2022 academic year. The Word Association Test was used as a data collection tool, and the key concepts of "environment" and "environmental problems" were given to the students and the students were made to make associations about these concepts. Then, the students were asked to make a sentence about the concepts of environment and environmental problems. Content analysis method was used in the analysis of the data obtained, and in this context, categories and codes were created for the answers given to the Word Association Test. The results regarding the key concept of "environment" were evaluated under five main themes: "ecosystem elements", "ecosystem types", "ecological concepts", "environmental problems" and "feelings and thoughts". The theme of ecosystem elements; the theme of “living elements”, “nonliving elements” and ecosystem varieties; “natural ecosystems” were examined under the subthemes “artificial ecosystems”. It can be said that the pre-service teachers who participated in the research have knowledge structures about the environment in general. However, pre-service teachers’ perceptions of the living environment show more diversity than their perceptions of the inanimate environment. It was observed that the number of answers regarding inanimate objects was low. Likewise, while making sentences about the environment, they mentioned inanimate objects very little. Other evocative words are ecological concepts that are quite numerous and varied. They also associated it with environmental problems. In addition to these, there are answers such as "we should be sensitive and conscious of the environment, we should protect it," in the perceptions of teacher candidates. It is important to have these in their perceptions, that is, to associate their feelings and thoughts with the environment. When the evaluation is made on the concepts that are associated rather than the number of answers given by the pre-service teachers, it has been revealed that they do not have a sufficient level of environmental perception. Student associations towards environmental problems; It has been expressed under the themes of "types of environmental problems", "reasons of environmental problems" and "results of environmental problems", and it has been determined that the connotations of pre-service teachers are gathered under the theme of "reasons of environmental problems". In their sentences, they talked more about the causes and consequences of environmental problems. It was determined that pre-service teachers made associations and formed sentences by addressing environmental problems more locally. As a result of the study, it was determined that the perceptions of the teacher candidates about the environment and environmental problems were not at a sufficient level and necessary suggestions were made in this regard.